The influence of CaF2/B2O3 ratios in calcium fluoroalumino borosilicate glass systems on glass ionomer cement performance - Ahmad Zahudi, Afrina Zulaikha; Amin, Khamirul Matori; Mohd Zaid, Mohd Hafiz; Yaakob, Yazid; Kul, Esra; Roslan, Zuraidah; Loh, Zhi Wei; Shah, Aishah Zarzali; Liza, Shahira (Springer Science and Business Media Deutschland GmbH, 2025)
Biocompatible glass ionomer cement (GIC) is commonly used in dental luting and filling restorative applications, but its mechanical limitations, such as high solubility and low wear resistance, restrict its use in stress-bearing areas. To enhance the performance of GIC, this research emphasizes the effect of different batch formulations of B₂O₃ and CaF₂ toward the calcium fluoroalumino borosilicate (CFABS) glass system on the structural, physical, and mechanical properties of GIC and investigates the incorporation of sustainable materials by substituting traditional SiO₂ and CaO with soda lime silica (SLS) and clam shell (CS) in the fabrication of CFABS glass via the conventional melt quenching technique. The CFABS glass system was synthesized with the chemical formulation: 21.25 SLS– 12.75 CS– 17 Al2O3– 17 P2O5– (32-x) CaF2- xB2O3 where x = 0–20 in weight% (wt%). XRD and FTIR showed that increasing the proportion of B₂O₃ reduced crystallinity while altering the glass structure through the formation of Si-O-Si and Si-O-B bonds. FESEM examination revealed a non-uniform particle distribution, however EDX analysis revealed that the calcium-to-phosphate molar ratio (Ca/P) of GIC samples was within the intended range of 1.72 to 2.29, supporting the formation of fluorapatite (Ca₅(PO₄)₃F). Density measurements indicated an increase from 1.526 g/cm³ to 1.833 g/cm³ as CaF₂ content rises. Compressive strength showed that GIC B3 with (22 wt%) amount of CaF₂ to (10 wt%) amount of B₂O₃ achieved the highest strength at 60.15 MPa, exceeding the ISO 9917-1:2007 standard of 50 MPa and comparable to commercial luting cements (50–70 MPa). Additionally, the highest value achieved for Vickers microhardness tests was 63.81 HV for GIC B3, in range with common marketplace products (50–90 HV). This study highlights the optimized composition with 22 wt% CaF₂ and 10 wt% B₂O₃ as a potential candidate for dental GIC applications, particularly in luting and base cement formulations, ensuring improved mechanical performance and clinical viability.